“The Monument of Wojtek the Bear” or Polish Projects to Commemorate Animals Involved in World War II - Lorenc, Magdalena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
A monument is not an imitation or representation of the past, but a cultural construct. The choice of a theme and the way it is presented in a monumental sculpture show what a particular group considered important and worthy of commemoration. Although it refers to the past, it is primarily concerned with the reality in which it was created. It is a response to a demand. The monuments of Wojtek which were founded in Poland in 2013–2014 contributed to the consolidation and dissemination of ideas about the bear-hero of Monte Cassino. By exposing patriotic themes and national symbols, the fate of the bear has been linked with the history of Poland during and after World War II. This clear and unequivocal message about the unusual relationship between Wojtek and the Anders’ Army soldiers does not mention how the animal was treated. Thus, the chance to problematize the fate of the bear in man’s captivity has been missed.

Pomnik nie jest imitacją czy reprezentacją przeszłości, lecz konstruktem kulturowym. Dobór tematu i sposób jego przedstawienia w rzeźbie pomnikowej, są świadectwem tego, co dana grupa uznała za ważne i godne upamiętnienia. I choć traktuje o tym, co minione, to przede wszystkim dotyczy rzeczywistości, w której został stworzony. Jest odpowiedzią na zapotrzebowanie. Powstałe w Polsce w latach 2013–2014 pomniki Wojtka, przyczyniły się do utrwalenia i rozpowszechnienia wyobrażeń o niedźwiedziu - bohaterze spod Monte Cassino. Eksponując wątki patriotyczne i symbole narodowe, losy niedźwiedzia powiązano z historią Polski w okresie i po zakończeniu drugiej wojny światowej. Dbałość o klarowny i jednoznaczny przekaz, którego treścią była nietypowa relacja między Wojtkiem i żołnierzami Armii Andersa, spowodowała pominięcie kwestii przedmiotowego traktowania zwierzęcia. Tym samym nie wykorzystano szans na sproblematyzowanie losów niedźwiedzia w niewoli człowieka.
Pomnik niedźwiedzia Wojtka
Keywords: Wojtek the Soldier Bear; statues of animals; animal-heroes; 2nd Polish Corps (Anders’ Army); battle of Monte Cassino; niedźwiedź Wojtek; pomniki zwierąt; zwierzę-bohater; 2 Korpus Polski (Armia Andersa); bitwa o Monte Cassino